Lung Infection by Human Bocavirus Induces the Release of Profibrotic Mediator Cytokines In Vivo and In Vitro - Khalfaoui, Soumaya (PLoS One, 2016)
Human Bocavirus subtype 1 (HBoV1) is associated with respiratory diseases and may contribute to chronic lung diseases by persisting in the infected host. Here the question was addressed if HBoV infections could contribute to fibrogenesis processes as suggested by previously published clinical observations. Cytokine profiles induced by HBoV infection in CuFi-8 air-liquid interphase cell cultures and in bronchoalveolar lavage fluid (BALF) of 20 HBoV-positive and 12 HBoV-negative patients were analysed by semi-quantitative Western spot blot analyses. Although lots of cytokines were regulated independently of HBoV status, several cytokines associated with lung fibrosis and tumour development, e.g., EGF, VEGF, TARC (CCL17), TNF-α, TNF-β, TIMP-1, were clearly upregulated in the HBoV-positive cohort. These findings suggest that the development of lung fibrosis might be triggered by HBoV induced cytokine expression.